Adaptive cabin suspension systems of commercial vehicles: a review of the state-of-art and future trends. (2nd June 2022) - Lu, Yukun; Khajepour, Amir; Liu, Yegang; Zhen, Ran
This paper reviews past studies on active and semi-active cabin suspension systems of commercial vehicles and highlights future research potentials. The development history of the cabin suspension is firstly introduced. Then, the three standard configurations on the market of the cabin suspension are discussed and compared, known as front, rear, and full cabin suspension systems. After that, an overview of cabin suspension control strategies in the literature is presented. Specifically, skyhook control, various optimal control, road adaptive control, and their combined approaches are discussed and compared. After thoroughly summarising past studies, some research topics which deserve further investigation are introduced.